Family sports intergenerational influence effect and related factors analysis in the Yangtze Delta of China - Yang, Kun; Liu, Wenduo; Song, Zhengxue (Frontiers in Psychology, 2025)
BackgroundThe intergenerational influence of family sports behavior is not only related to the interaction and imitation between the two generations, but also to factors such as family culture and socioeconomic status.ObjectiveThis study aims to investigate the intergenerational influence and determinants of family physical activity behavior in the Yangtze River Delta region of China.MethodsThis study investigated sports motivation, sports conditions, and sports rating through parent–child scales distributed to 288 families with school-age children aged 9–19 in the same area. Information on the gender and age of the children in each family, as well as the age, occupation, income, and educational background of the parents, was collected. Finally, the above results were statistically analyzed using the t-test and One-way analysis of variance.ResultsThe results show that caregiving parents’ gender has a significant impact on offspring sports motivation (OSM). The differences in the occupations of their parents have a significant impact on OSM, Offspring Sports Rating (OSR), and Offspring Sports Condition (OSC), and the sports-related occupations parents have a significant positive effect on the development of their offspring’s sports behavior. As well as differences in the educational background of their parents have a significant impact on OSC. On the other hand, the offspring’s influence on parental sports motivation (PSM) varies at different ages.ConclusionParental gender, education, occupation and children’s age are the key factors in the intergenerational influence of family sports behavior in the Yangtze River Delta region of China.